Comparision of intra cervical PGE2 gel and transcervical Foley’s catheter for pre-induction cervical ripening - Singh, Vaishali; Nath, Paras (Clinical Journal of Obstetrics and Gynecology, 2022)
Introduction: Induction of labour is a common obstetric intervention, occurring in approximately 25% of term pregnancies in developing countries. Pharmacological and mechanical methods commonly used are prostaglandin preparations (PGE1 and PGE2) and various intracervical catheters (single or double balloon), respectively. Material and methods: Study was conducted in Siliguri District Hospital, Siliguri, Darjeeling, west Bengal. 100 antenatal woman admitted in obstetrics ward with pog more than 37 weeks were taken for study after applying inclusion and exclusion criteria. 50 were induced with cerviprime gel and 50 with intracervical foley catheter. Statistical analysis done. Results: Mean interval between treatment initiation and delivery was not statistically significant, tachysystole was more common in group B women, rate of LSCS and NVD was similar in both groups. Conclusion: It can be concluded from the present study that Foley’s catheter (mechanical) and prostaglandin E2 gel [pharmacological] both are effective agents for preinduction cervical ripening which substantially improve the bishops score and increase the chances of successful labour induction. There is no significant difference in their efficacy, mode of delivery and perinatal outcome.